1994
DOI: 10.1021/bi00183a006
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Distinct MDR Modulators Show Specific Patterns of Reversal Against P-Glycoproteins Bearing Unique Mutations at Serine939/941

Abstract: The mechanism by which P-glycoprotein (P-gp) interacts with a number of structurally unrelated substrates or inhibitors remains unknown. We have recently shown that a serine residue within the predicted transmembrane (TM) domain 11 of P-gps encoded by mouse mdr1 (Ser941) and mdr3 (Ser939) plays an important role in the substrate specificity of P-gp. We wished to determine if Ser939/941 is also important for efficient interaction of P-gp with structurally different modulating agents, a cyclic peptide (cyclospor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 48 publications
2
43
1
Order By: Relevance
“…The stimulatory effect in nematodes may be due either to an upregulation resulting in an increase in the number of active Pgp proteins recruited to the surfaces of the parasites (for a review, see reference 59) or to an increased rate of efflux by Pgp already present at the time of addition of R123 coupled with anthelmintics or other compounds. Several chemically unrelated compounds have been identified as "inducers" of Pgp synthesis, such as colchicine (24,26,66), daunorubicin (8,57), vinblastine (1,54,57), and vincristine (54,66). However, our study of the dynamics of R123 efflux, observed within a few minutes after addition of anthelmintics, is not compatible with such upregulation but rather points to Pgp already present near or at the surface of the parasite.…”
Section: Fig 3 Effects Of Classically Used Pgp Substrates On R123 Econtrasting
confidence: 52%
See 1 more Smart Citation
“…The stimulatory effect in nematodes may be due either to an upregulation resulting in an increase in the number of active Pgp proteins recruited to the surfaces of the parasites (for a review, see reference 59) or to an increased rate of efflux by Pgp already present at the time of addition of R123 coupled with anthelmintics or other compounds. Several chemically unrelated compounds have been identified as "inducers" of Pgp synthesis, such as colchicine (24,26,66), daunorubicin (8,57), vinblastine (1,54,57), and vincristine (54,66). However, our study of the dynamics of R123 efflux, observed within a few minutes after addition of anthelmintics, is not compatible with such upregulation but rather points to Pgp already present near or at the surface of the parasite.…”
Section: Fig 3 Effects Of Classically Used Pgp Substrates On R123 Econtrasting
confidence: 52%
“…The regression lines, obtained from the log agonist versus response variable-slope model by use of Prism software, were significant for all compounds (P Ͻ 0.001). (16,26,54). In addition to ivermectin, several other macrocyclic lactones were also demonstrated to affect R123 transport, using two vertebrate cell lines transfected with murine or human Pgp genes (35).…”
Section: Fig 3 Effects Of Classically Used Pgp Substrates On R123 Ementioning
confidence: 99%
“…Several lines of evidence measuring transport, binding and ATPase activity of P-gp have pointed to the presence of multiple drug interaction sites (Ferry et al, 1992(Ferry et al, , 1995Spoelstra et al, 1992;Malkhandi et al, 1994;Ayesh et al, 1996;Orlowski et al, 1996;Martin et al, 1997). CP100-356 is a diaminoquinazoline and amongst the most potent MDR-modulating agents reported (Kajiji et al, 1994), hence providing specificity and selectivity of binding displacement. The modest difference in the affinity of P-gp1a and P-gp1b for CP100-356, estimated by its ability to displace vinblastine binding, and similar modest differences for verapamil, are unlikely to account for the duplication of the two drug transporting P-gp isoforms in mouse.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by saturation of efflux occurring at concentrations spanning the P-gp K m . Furthermore, studies in Caco-2 monolayers with the P-gp inhibitors verapamil and CP-100,356 (Kajiji et al, 1994;Pauli-Magnus et al, 2000) resulted in a reduction of efflux ratio to near unity. Since UK-294,315 is a P-gp substrate and this property is considered responsible for nonlinearity in Caco-2 experiments, it is likely that this is also the case in humans.…”
Section: Fig 5 Mean Pharmacokinetic Profiles After Oral Administratmentioning
confidence: 99%